Sinonasal Disease in Total Laryngectomy Patients. (September 2019) - Patel, Vijay A.; Pool, Christopher D.; Dunklebarger, Mitchell; Schaefer, Eric; Goyal, Neerav
Objective: Total laryngectomy (TL) results in complete abolition of nasal airflow, with notable pathologic alterations of the intranasal mucosa, mucociliary clearance, and nasal cycle. Despite these observed morphological changes, it remains unclear whether this subpopulation of patients experiences clinically significant sinonasal disease. The goal of this study was to identify rhinosinusitis in TL patients using radiographic imaging. Methods: An Institutional Review Board–approved retrospective review (January 2005-July 2017) identified 50 patients who underwent radiographic imaging before and after TL. The Lund-Mackay Staging System (LM) was applied to 197 surveillance computed tomography scans. Surveyed patients also underwent investigation of current sinonasal symptomatology using the SNOT-22 questionnaire. Simple linear regression was modeled to LM scores; tests of statistical significance were estimated via the method of Kenward and Roger. Results: The mean age was 62.4 years, with a 5:1 male-to-female ratio. The mean SNOT-22 score was 27.4 (range, 5-33). A median of 3 scans was obtained, 49% within 12 months after TL. The mean (± standard deviation) postoperative LM score was 2.7 ± 3.97 points (range, 0-19). For every 1 month after TL, postoperative LM was +0.01 point ( P = .49). Conversely, for every +1 point in preoperative LM, postoperative LM was +1.08 points ( P < .001). Two patients required functional endoscopic sinus surgery after TL for persistent sinonasal disease. Conclusions: Preoperative sinonasal disease burden likely plays an important role in the development of clinically significant rhinosinusitis in TL patients. Correlating radiographic findings to validated outcome measures remains a critical aspect of determining optimal surgical candidates; this arena is still under investigation in this unique patient cohort.